NECESSITY OF MAPPING AND ASSESSMENT OF ECOSYSTEMS AND THEIR SERVICES IN PLANNING AND DECISION MAKING PROCESS - Brūniņa, Līga; Konstantinova, Elīna; Peršēvica, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The EU Biodiversity Strategy to 2020 determines that “Member States, with the assistance of the Commission, will map and assess the state of ecosystems and their services in their national territory by 2014, assess the economic value of such services, and promote the integration of these values into accounting and reporting systems at EU and national level by 2020”. Mapping and assessment of ecosystem services provides several benefits, one of which is baseline data providing to measure net future gains or losses and data integration into spatial development process. The aim of the paper is to present and discuss the approach taken to assessing ecosystem services in order to introduce necessity of mapping and assessment of ecosystems and their services for planning and decision-making process in Latvia. The paper will focus on terminology interpretation of ecosystem services, introducing with set of developed indicators for assessment of ecosystem services and define appropriate for Latvia. The paper closes with estimation of potential benefits and necessity to integrate assessment of ecosystems services in spatial planning and decision-making process.